Oxaliplatin-induced type II hypersensitivity in colorectal cancer: a cohort study on clinical presentation, diagnosis, and management - Vázquez-Revuelta, Paula; Madrigal-Burgaleta, Ricardo; Ruffinelli, J. Carlos; Casanovas, Enric; Coloma, Ana; Lleonart, Ramon (Frontiers in Pharmacology, 2025)
BackgroundOxaliplatin (OXL) is a key treatment for colorectal cancer but can potentially induce type II hypersensitivity reactions (II-HSRs), leading to immune-mediated cytopenias. The prevalence and management of OXL-induced II-HSRs remain poorly understood, with evidence being mainly anecdotal and lacking a systematic approach. This study examines the prevalence, clinical presentation, diagnosis, and management of OXL-induced II-HSRs in our population.MethodsWe prospectively analysed a cohort of OXL-reactive patients at our Drug Hypersensitivity and Desensitisation Centre between January 2019 and April 2024. Patients with clinical and laboratory findings suggestive of II-HSR were included and classified into acute immune thrombocytopenia (AIT), immune haemolytic anaemia (IHA), Evans syndrome (ES), or drug-induced thrombotic microangiopathy (DITMA). Drug-dependent antibodies (DDAbs) were detected via flow cytometry. Carefully selected patients underwent re-exposure to OXL under allergy care and special safety measures.ResultsSixteen patients were diagnosed with II-HSRs, with a prevalence of 9.5% among OXL-reactive patients. The mean number of OXL cycles at onset was 20. Atypical hypersensitivity symptoms such as chills, fever, and back pain aided clinical identification. AIT was the most common presentation (56%), followed by ES (38%), and one case of DITMA (6%). DDAbs were detected in 86% of cases, with two patients showing DDAbs to other drugs. Five selected patients were re-exposed to OXL without significant complications.ConclusionOXL-induced II-HSRs are rare but pose diagnostic and management challenges. This study shows the importance of early identification, the potential role of DDAbs testing, and the feasibility of re-exposure under controlled conditions in selected patients.